2017
DOI: 10.1002/2017gl073279
|View full text |Cite
|
Sign up to set email alerts
|

Thermoremanence acquisition and demagnetization for titanomagnetite under lithospheric pressures

Abstract: The geological sources of large‐scale lithospheric magnetic field anomalies are poorly constrained. Understanding the magnetic behavior of rocks and minerals under the pressures and temperatures encountered at large crustal depths is particularly important in that task. The impact of lithospheric pressure is not well known and most of the time neglected in numerical models of the geological sources of magnetic anomalies. We present thermal remanent magnetization (TRM) acquisition and stepwise thermal demagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Some sedimentary rocks have shown strong dependence to metamorphism (Rochette, 1987), but it is mainly magnetite breakdown and pyrrhotite creation, which at high grade conserve magnetic susceptibility. Since none of our samples show any sign of such modifications, and given that magnetic sources can subsist even at great depth (Demory et al, 2013;Ferré et al, 2013;Li et al, 2015;Launay et al, 2017), it FIGURE 11 | Model of the crustal structure along profile C beneath the WAMA considering deep BIFs with remanence and without magnetic lower crust. The parameters are identical to the ones in Figure 8.…”
Section: Discussionmentioning
confidence: 97%
“…Some sedimentary rocks have shown strong dependence to metamorphism (Rochette, 1987), but it is mainly magnetite breakdown and pyrrhotite creation, which at high grade conserve magnetic susceptibility. Since none of our samples show any sign of such modifications, and given that magnetic sources can subsist even at great depth (Demory et al, 2013;Ferré et al, 2013;Li et al, 2015;Launay et al, 2017), it FIGURE 11 | Model of the crustal structure along profile C beneath the WAMA considering deep BIFs with remanence and without magnetic lower crust. The parameters are identical to the ones in Figure 8.…”
Section: Discussionmentioning
confidence: 97%
“…Magnetostriction increases strongly with the Ti content of magnetite and could result in a much stronger PRM acquisition for Ti‐substituted magnetites. This can lead to significantly higher crustal magnetizations when the TRM/PRM is acquired under pressure rather than at ambient pressure (Launay et al, ). This could have implications for the interpretation of magnetic anomalies in oceanic crust, where the main magnetic carriers are Ti‐magnetite (TM60).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the effect of eventual remanence, in the absence of magnetization measurements on samples from cores of deep drillings, one cannot really investigate it. A recent study has however shown that it should be taken into account in the middle and lower crusts (Launay et al, 2017(Launay et al, , 2018. Fig.…”
Section: Figurementioning
confidence: 99%